Reading in the Zoopolis: Review of Aaron M. Moe, Zoopoetics: Animals and the Making of Poetry - Googasian, Vicky (Humanimalia, 2014)
Aaron M. Moe. Zoopoetics: Animals and the Making of Poetry. Lanham, MD: Lexington Books, 2014. 150 pp. 80 (hb).